Koko kantopinnan käsitely tärkeintä kantokäsittelyn onnistumiselle - Poteri, Marja (Metsäntutkimuslaitos, 2008)
Selostus artikkelista: Rönnberg, J., Sidorov, E. & Petrylaite, E. 2006. Efficacy of different concentrations of Rotstop® and Rotstop® S and imperfect coverage of Rotstop® S against Heterobasidion spp. spore infections on Norway spruce stumps. Forest Pathology 26: 422-433